Association between trimethylamine N-oxide and prognosis of patients with myocardial infarction: a meta-analysis - Xiuqing Li; Yubao Wang; Jie Xu; Kaili Luo; Tao Dong (Frontiers in Cardiovascular Medicine)
BackgroundTrimethylamine N-oxide (TMAO) has been widely explored and considered as a biomarker for adverse cardiovascular events. However, the relationships between TMAO adverse cardiovascular events are inconsistent in patients. Therefore, this meta-analysis aimed to estimate association between TMAO levels and the prognosis of patients with myocardial infarction (MI).MethodsWe searched PubMed, EMBASE, the Cochrane Library, and Web of Science from inception to July 2, 2023, to retrieve all relevant clinical trials. Associations between TMAO levels, major adverse cardiovascular events (MACE), all-cause mortality, recurrent MI, stroke, etc., were systematically addressed. Outcomes included MACE, all-cause mortality, recurrent MI, rehospitalization caused by heart failure, stroke, revascularization, SYNTAX score, and multivessel disease. A fixed/random-effects model should be adopted to calculate the pooled estimates. Besides, funnel plot, Begg's test and Egger' test were used to test publication bias.ResultsA total of nine studies were included in our meta-analysis. Our results indicated that higher TMAO levels were associated with greater risk of MACE (RR = 1.94; 95% CI = 1.39 to 2.73), all-cause mortality (RR = 1.56; 95% CI = 1.00 to 2.44), and MI (RR = 1.21; 95% CI = 1.01 to 1.45). No significant association was found in stroke, SYNTAX, and multivessel disease. Besides, our results reported that the association between TMAO levels and MACE after MI was not affected by the geographic localization.ConclusionThis study was the first meta-analysis that showed a significant positive association of TMAO levels with MACE, all-cause mortality, and recurrent MI in patients with MI.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=460400, PROSPERO (CRD42023460400).